(untitled) (Tempo e Argumento, 2020)
This article investigates concepts of aesthetics, such as the grotesque and the feminine grotesque, the Bergsonian understanding of laugh and the feminist studies about body and gender, in the analysis of humor strategies in the Graphic Novel The fruit of knowledge (2018). We noticed the repetitions and inversions promoted by the author Liv Strömquist, when proposing a history of the female genitalia - its mutilations, restrictions and interdictions - and the consequent laughter by confronting historical hierarchies and incongruencies. As a main result, we observed a feminist aesthetic carried out by laughter, in a reading that provides reflection on the place of women authorship and the political images of body and corporalities spread in our society. Keywords: Feminism. Graphic Humour. Comic Books.